ANALISIS PENGARUH CR DAN ROE TERHADAP PER PADA PT. INDOFOOD SUKSES MAKMUR TBK TAHUN 2011-2018 - Firanti Hardianti; Sukma Febrianti (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2021)
PER is an important ratio in analyzing stocks, research was conducted at PT. Indofood Sukses Makmur Tbk by using two ratios as analysis tools, namely CR and ROE. The author chooses to conduct research at PT. Indofood Sukses Makmur Tbk because it is the largest consumer food company compared to its peers in Indonesia. This research was conducted to see the effect of CR and ROE simultaneously, partially and dominantly on PER using quantitative descriptive methods. The results showed that the data used were normal using the normal probability test plot. If using multiple linear regression test, the CR has a unidirectional relationship, while the ROE is not in the same direction as the PER. The results of hypothesis testing using the F test and t test. The F test states that the CR and ROE have a simultaneous effect and the t test partially affects the PER. To see how much influence the independent variable has on the dependent variable, a determination coefficient test is carried out with the result that the independent variable is quite influential on the dependent variable by 79.5%, and finally the dominant test with the results of ROE which has the most influence on the PER